Investigating charge dynamics at lead halide perovskite single crystal surfaces - Birgit Kammlander; Alberto García-Fernández; Sebastian Svanström; Erika Giangrisostomi; Ruslan Ovsyannikov; Håkan Rensmo; Ute B Cappel (JPhys Energy)
To further develop lead halide perovskites for their application in solar cells, understanding the material’s fundamental behavior under illumination is necessary. Investigating light-induced charge dynamics in single crystals can give insight into material inherent properties. Time-resolved photoelectron spectroscopy (TR-PES) allows to monitor the photovoltage build-up and decay between the sample surface and bulk over time and gives information on light-induced charge redistribution within the crystal. Additionally, this method enables us to follow compositional changes and surface degradation and distinguish these from purely electronic effects. Here we investigated the charge dynamics of two distinct lead halide perovskite single crystal surfaces (CsPbBr _3 , Cs-doped FAPbI _3 ) using TR-PES in different timescales (ps to μ s and s to min). It was found that CsPbBr _3 shows photovoltage rise and decay on the nanosecond to microsecond time-range, which can be assigned to electron–hole pair separation between surface and bulk. On the other hand, such electron dynamics could not be resolved for Cs-doped FAPbI _3 at these fast timescales. Instead, for Cs-doped FAPbI _3 , the observed photovoltage decay was dominated by much slower dynamics and relaxation to the dark equilibrium state took around 10 min. This suggests that ion migration is responsible for a photovoltage build-up between surface and bulk of the crystal.